PRACTISING MARITIME ENGLISH VOCABULARY AND DEVELOPING ACCURACY THROUGH Ã¢â¬ËTHE WALL DICTATIONÃ¢â¬â¢ - Setiyaningsih, Nita (Language Circle: Journal of Language and Literature, 2009)
With more and more multi-lingual and multicultural crews joining the transnational seafarersÃ¢â¬â¢ maritime community, their competence in maritime English (Maritime ESP) becomes a public concern. There is a need for maritime English lecturers to use some effective techniques in teaching maritime English vocabulary so that students can master it well. The presentation of new vocabulary should be followed up immediately with controlled practice. Ã¢â¬ËWall DictationÃ¢â¬â¢ is suggested since it not only can be used for practising vocabularies but also can be used for developing accuracy which leads to clear communication. ÃÂ  Keywords: maritime English vocabulary; accuracy; dictation